The dispensation of the Báb - Handal, Boris ([Kellyville, New South Wales] : Boris Handal, 2023)
A systematic overview of the Báb’s theological and legal teachings, the Bábí Faith, and prophecies relating to Bahá’u’lláh in the Bábí scriptures. Prepared and categorised in an accessible manner for Western readers for the first time.
Includes bibliographical references and index.
Keywords: Bāb, ʻAlī Muḥammad Shīrāzī, -- 1819-1850 -- Teachings; Babism; Babism -- Biography; Australian; Biographies